Intervenção psicopedagógica e dislexia: um relato de caso clínico - Oliveira, Marina Costa Oliveira e (2016)
This article aims to report a clinical psychopedagogical intervention with a child with symptoms of dyslexia. The choice of this object of study was based on a case study carried out in compliance with the discipline of Supervised Clinical Stage, in which it requires the work of evaluation and intervention of the person in attendance. As a starting point, the complainant was referred to the difficulty of reading and writing, and that it presents an illegible handwriting. From the initiation of the evaluation of the case study, we verified the possible contributions of clinical psychopedagogical interventions to work together with a child with a diagnosis of dyslexia, being performed preventively and therapeutically to improve the development of the individual's reading. Methodologically, the research is characterized as a clinical case study, with an exploratory approach, based on qualitative research, as it attends to the understanding and analysis of the case through the evaluation and interventions performed, in which the person in care developed indications for reading. In this specific case, the child is 8 years old and attends the 3rd year of Elementary School I and does not read anything at all, although it does not have age / grade distortion. We believe that this work is relevant and will bring contributions to psychopedagogy, in the sense of offering ways to intervene with a child who has the same difficulty as the case study.